2017
DOI: 10.1002/9781119227250.ch12
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscope Imaging Sharpens Geochronological Interpretation of Zircon and Monazite

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…However, the proximity of the Group 1 analytical spots to the Neoproterozoic domains suggests a degree of analytical mixing for the Group 1 results. It is also possible that Neoproterozoic domains were incompletely dissolved adjacent to the dissolution-reprecipitation interface and remain within the Group 1 domains (Seydoux-Guillaume et al 2018;Williams et al 2011). Therefore, we do not attach any geological significance to the Group 1 age of 502 ± 15 Ma.…”
Section: Timing Of Events Recorded By Monazitementioning
confidence: 91%
See 1 more Smart Citation
“…However, the proximity of the Group 1 analytical spots to the Neoproterozoic domains suggests a degree of analytical mixing for the Group 1 results. It is also possible that Neoproterozoic domains were incompletely dissolved adjacent to the dissolution-reprecipitation interface and remain within the Group 1 domains (Seydoux-Guillaume et al 2018;Williams et al 2011). Therefore, we do not attach any geological significance to the Group 1 age of 502 ± 15 Ma.…”
Section: Timing Of Events Recorded By Monazitementioning
confidence: 91%
“…Holder et al (2015) revealed significant concentrations of common-Pb in monazite which formed via dissolution-reprecipitation of older monazite in UHP conditions. To add further uncertainty, dissolution-reprecipitation experiments coupled with transmission electron microscopy have revealed relic, nano-scale domains of older monazite preserved in the younger, reprecipitated monazite (Seydoux-Guillaume et al 2018). Monazite that grows in sub-UHP conditions, however, typically has little to no incorporation of common-Pb (Montel et al 1996).…”
Section: Timing Of Events Recorded By Monazitementioning
confidence: 99%
“…In samples SN18-05A and SN18-12, the lack of distinct REE precursor for monazite allows the possibility of dissolution-reprecipitation driven by these greenschist-facies fluids. However, this process has been documented to result in disequilibrium Pb distribution, producing anomalously old ages within reprecipitated monazite domains [61,62], or inheriting relic domains of the starting monazite material within reprecipitated monazite [61]. The lack of distinct chemical populations amongst the analyzed monazite certainly suggests chemical disequilibrium and perhaps mixed monazite chemistry (Figure 6).…”
Section: Extraneous Pb In Monazitementioning
confidence: 99%
“…These studies typically use an advanced analytical workflow to constrain the scale of Pb mobility and the timing of isolation of Pb from parental U and Th (Peterman et al, 2016;Seydoux-Guillaume et al, 2019;Valley et al, 2015). This approach, which integrates textural, microstructural, compositional and isotopic analyses from the micro-to the nanoscale yields significant advances on the causes of isotopic discordance and ages variation at the microscale (Peterman et al, 2016;Seydoux-Guillaume et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%